2016
DOI: 10.1080/02699052.2016.1179792
|View full text |Cite
|
Sign up to set email alerts
|

Blood biomarkers indicate mild neuroaxonal injury and increased amyloidβproduction after transient hypoxia during breath-hold diving

Abstract: The findings suggest that transient hypoxia may acutely increase the levels of Aβ42 and T-tau in plasma of healthy adults, further supporting that general hypoxia may cause mild neuronal dysfunction or damage and stimulate Aβ production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Notably, [S100B] is still significantly elevated five days after a dynamic apnea that resulted in hypoxic syncope (Linér and Andersson 2009), highlighting the long-lasting negative consequences of a NNE. Such findings were confirmed by Gren and colleagues (Gren et al 2016) who reported an altered amyloid metabolism reflecting neuronal damage or dysfunction after a maximal static apnea (mean apneic time: 302 sec, range 138-457 sec) performed during a national championship. An accumulation of amyloid precursor protein is typically found in patients with traumatic brain injury (Baugh et al 2012), which strengthens the evidence for the strong debilitating impact of a BH episode held to one's maximal capacity for the integrity of the central nervous system.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Notably, [S100B] is still significantly elevated five days after a dynamic apnea that resulted in hypoxic syncope (Linér and Andersson 2009), highlighting the long-lasting negative consequences of a NNE. Such findings were confirmed by Gren and colleagues (Gren et al 2016) who reported an altered amyloid metabolism reflecting neuronal damage or dysfunction after a maximal static apnea (mean apneic time: 302 sec, range 138-457 sec) performed during a national championship. An accumulation of amyloid precursor protein is typically found in patients with traumatic brain injury (Baugh et al 2012), which strengthens the evidence for the strong debilitating impact of a BH episode held to one's maximal capacity for the integrity of the central nervous system.…”
Section: Discussionsupporting
confidence: 57%
“…An accumulation of amyloid precursor protein is typically found in patients with traumatic brain injury (Baugh et al 2012), which strengthens the evidence for the strong debilitating impact of a BH episode held to one's maximal capacity for the integrity of the central nervous system. Interestingly, the level of total tau structural protein, which serves to maintain grey matter cortical interneurons integrity and functionality, was also positively correlated with apneic time (Gren et al 2016). One may therefore argue that repeated exposures to such transient, severe hypoxia leads to chronic negative consequences in diver populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the extent to which repeated and prolonged exposure to these physiological extremes of hypoxaemia, alkalosis and acidosis has an adverse impact on the brain remains an open question, although emergent magnetic resonance imaging and immunochemical data suggest an association with structural brain damage and long-term cognitive complications (Andersson, Liner, & Jonsson, 2009;Bailey, Bartsch, Knauth, & Baumgartner, 2009;Gren et al, 2016). This has been linked to disrupted redox homeostasis characterized by excessive free radical formation, reflecting a shift from a physiologically adaptive (hormetic) to a pathologically maladaptive (damaged) phenotype (Bailey et al, 2013(Bailey et al, , 2019).…”
Section: Pushing the Limits; The Brain's Bioenergetic Tightropementioning
confidence: 99%
“…Notwithstanding the uncertainties associated with acidbase adjustments and corresponding shifts in the O 2 -Hb dissociation curve as outlined, these calculations are at the very least hypothesis testing and demonstrate that these athletes are operating very close to, if not indeed at, the very limit of human consciousness, findings corroborated by the high incidence of LOC and loss of motor control (confusion, loss of postural control, faltering vision, speech problems) recorded among competitive freedivers, clinical signs that are the frustrating cause for disqualification. Furthermore, emerging MRI and immunochemical evidence suggests that extremes of freediving and high-altitude mountaineering may be associated with structural brain damage (Bailey et al, 2009a;Gren et al, 2016) with potential long-term neuropsychological consequences. This contrasts with the extraordinary hypoxia tolerance exhibited by diving mammals, including the seal that is capable of enduring PaO 2 's as low as 7-10 mmHg without cerebral integrity being compromised (Elsner et al, 1970).…”
Section: Pushing the Limits Of Hypoxemia And Hyperemiamentioning
confidence: 99%